2015
DOI: 10.1111/hiv.12289
|View full text |Cite
|
Sign up to set email alerts
|

Independent association of subclinical coronary artery disease and emphysema in HIV‐infected patients

Abstract: In this cross-sectional study of HIV-infected patients, there was an independent association between emphysema and CAC, after adjustment for traditional cardiovascular risk factors, suggesting a common pathogenesis of these chronic inflammatory conditions in a chronic inflammatory disease such as HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
12
1
1
Order By: Relevance
“…Emphysema has also been associated with extrapulmonary inflammatory diseases, such as non-obstructive coronary artery disease, in HIV. [41] Of note, in this study we found a trend towards higher sCD14, in subjects with emphysema but no significant association, which may challenge the role of monocyte-specific inflammation in emphysema among those with HIV. [4]…”
Section: Discussioncontrasting
confidence: 55%
“…Emphysema has also been associated with extrapulmonary inflammatory diseases, such as non-obstructive coronary artery disease, in HIV. [41] Of note, in this study we found a trend towards higher sCD14, in subjects with emphysema but no significant association, which may challenge the role of monocyte-specific inflammation in emphysema among those with HIV. [4]…”
Section: Discussioncontrasting
confidence: 55%
“…Only one prior study has examined the relationship between lung disease and CAD, to our knowledge (43). In this study, Agatston CAC scores and visual emphysema scores were assessed using EKG-gated cardiac CT scans.…”
Section: Original Researchmentioning
confidence: 99%
“…We do have concerns that lung disease remains undertreated among PLWH, as previous studies from SHIELD demonstrated that nearly 25% of those with severe COPD were not even aware of their diagnosis of COPD 30 . Previous studies have also suggested that worsened pulmonary disease goes hand and hand with progression of other HIV related comorbidities 31,32 . While we did adjust for the presence of several comorbidities, our analysis was unable to account for severity of disease in a number of important comorbidities, including cardiovascular disease and renal failure.…”
Section: Discussionmentioning
confidence: 99%